The Equivalences between Ideas of Abd al-âQahir al-Jurjani and Structural Linguistics âand the New Criticism - روح الله هادی; لیلا سید قاسم (مطالعات زبانی و بلاغی)
Abd al-Qahir al-Jurjani (400 â 471 AH / 1078 AD), the âcelebrated Persian rhetorician and grammarian, inaugurated âthe Arab linguistic revolution through his seminal works, ânamely Asrar al-Balaghah (The Secrets of Elucidation) and âparticularly Dala'il al-I'jaz (Intimations of Inimitability). In âthe recent century, after efforts of Muhammad Abduh in âEgypt to revive the Islamic scientific thought, editing and âprinting of Jurjaniâs scripts was prospered. Immediately after, âthe novelty of his ideas drew the attention of many scholars, âand initiated a widespread quest to find the similarities of his âideas with modern linguistics, in theory and practice. This âendeavor which perhaps is in its midway, led to find many âequivalences and has produced remarkable results.â It is the aim of this article to analyze some ideas of âJurjani from Dala'il al-I'jaz which collectively are known as âââThe Theory of Nazmâ, and deliberate those equivalences âwith structural linguistics and the new criticism. Word (lafáº) âand meaning (maÊ¿ÄnÄ«), the syntagmatic and paradigmatic âaxes, and differences of langue and parole are the most âimportant topics that inter-relate Jurjani with contemporary âlinguistics. The principal equality of Jurjani and structural âlinguistics is his perception of language as a system of âcommunication.â